Theoretical study on FRP-confined rectangular columns considering rebar buckling - Sun, Peng-Xuan; Bai, Yu-Lei (Construction & building materials, 2024)
Steel rebar buckling is an important failure mode in reinforced concrete (RC) columns. Fiber-reinforced polymer (FRP) composites provide an effective mean that can restrain or delay longitudinal rebar buckling. To accurately predict the strength and ductility of FRP-strengthened rectangular RC columns, it is necessary to accurately evaluate the interactions between FRP confinement and steel reinforcement buckling behavior at as any loading levels as possible. This paper proposed a composite beam model and a tension-bending beam model to evaluate the lateral support stiffness of FRP-wrapped concrete cover on steel reinforcement in the corner regions and flat sides of rectangular columns. Then, the whole stress-strain curves for reinforcing bar buckling behavior considering the lateral support of FRP jackets can be obtained and validated with the existing test database. For FRP-strengthened rectangular RC columns under monotonic axial compression, the overall load-bearing capacity of RC columns can be determined by summarizing axial loads sustained by FRP-confined corresponding plain concrete (PC) columns and the load contribution of steel rebars considering FRP lateral support. The accuracy of the proposed method is demonstrated by comparing theoretical predictions with test results. This calculation method can accurately predict the strength and ductility of FRP-wrapped rectangular columns within a 20% variation margin, which provides a reliable basis for the design of concrete structures. •A composite beam model and a tension-bending beam model are developed to evaluate the spring stiffness.•A method is established to predict the overall behavior of FRP-confined rectangular RC columns considering bar buckling.•The factors affecting rebar buckling and the performance of FRP-confined rectangular RC columns are analyzed.